2019
DOI: 10.4168/aair.2019.11.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Associated With Activated Eosinophils Contribute to the Pathogenesis of Aspirin-Exacerbated Respiratory Disease?

Abstract: Eosinophils have long been recognized as a central effector cell in the lungs of asthmatic patients. They contribute to airway inflammation and remodeling through releasing several molecules such as cytokines, granule proteins, lipid mediators and extracellular traps/vesicles. Repeated evidence reveals that intense eosinophil infiltration in upper and lower airway mucosae contributes to the pathogenesis of aspirin-exacerbated respiratory disease (AERD). Persistent eosinophilia is found to be associated with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…It was shown that ILC2s are recruited to nasal mucosa of NERD patients after COX‐1 inhibitor administration, correlating with enhanced production of prostaglandins and leukotrienes . Concurrently, ILC2s activate and recruit mast cells and eosinophils by production of cytokines such as IL‐5 and IL‐9 but in a response to released PGD 2 and cysLTs ILC2s are activated. These observations show how complex the pathogenesis of aspirin exacerbated disease is, including not only the alternations in eicosanoid production after COX‐1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that ILC2s are recruited to nasal mucosa of NERD patients after COX‐1 inhibitor administration, correlating with enhanced production of prostaglandins and leukotrienes . Concurrently, ILC2s activate and recruit mast cells and eosinophils by production of cytokines such as IL‐5 and IL‐9 but in a response to released PGD 2 and cysLTs ILC2s are activated. These observations show how complex the pathogenesis of aspirin exacerbated disease is, including not only the alternations in eicosanoid production after COX‐1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, accumulating evidences revealed that cytolysis could represent the occurrence of extracellular trap cell death (ETosis) [37][38][39]. ETosis represents a suicidal cell death process originally found in human neutrophils (i.e., neutrophil extracellular trap cell death (NETosis)) [40].…”
Section: Cytolytic Etosis Mediates Clc Formationmentioning
confidence: 99%
“…The key inflammatory cells in NERD are eosinophils and mast cells, which are closely interacting with other inflammatory and structural cells including basophils, platelets, neutrophils and epithelial cells. Regarding the activation mechanisms of eosinophils, both Th2 cells and ILC2 could activate eosinophils via release of IL-4, IL-5 and IL-13; moreover, activated eosinophils release the eosinophil extracellular traps (EETs), enhancing type 2 inflammation via interacting with epithelial cells and autocrine functions of eosinophils in the asthmatic airway ( Pham et al., 2017 ; Choi et al., 2019b ; Yin et al., 2020 ). There have been some data demonstrating epithelial dysfunction related to type 2 inflammation in NERD: 1) lower levels of SPD (protective function against eosinophilia) ( Choi et al., 2019a ), 2) increased epithelial folliculin and periostin levels ( Kim M. A. et al., 2014 ; Trinh et al., 2018 ; Choi et al., 2019b ), 3) increased CysLT-induced signaling (binding to CysLT2R or CysLT3R) in airway epithelial cells to induce the release of pro-inflammatory cytokines including IL-33, TSLP and IL-25 ( Corrigan et al., 2005 ), leading to type 2/eosinophilic inflammation and remodeling in NERD ( Ulambayar et al., 2019 ).…”
Section: Pathophysiologymentioning
confidence: 99%